INTEGRATION OF ETHNO-BIOLOGY AND INDIGENOUS KNOWLEDGE SYSTEMS (IKS) IN SECONDARY SCHOOL BIOLOGY: EFFECTS ON STUDENT ENGAGEMENT, CONCEPTUAL UNDERSTANDING, AND RETENTION IN SOUTH-EAST NIGERIA - Esther Ebele Akachukwu; Okoye Paschal Olisaeloka (Universitas Ngeri Malang, 2025)
Persistent reports from the West African Examinations Council (WAEC) and the National Examinations Council (NECO) reveal that secondary school students in Nigeria struggle to grasp abstract concepts in Biology, particularly in areas such as genetics, ecology, and cellular respiration. At the same time, students in South-East Nigeria exhibit a profound, practical understanding of local flora and fauna (for instance, the medicinal applications of Vernonia amygdalina (bitter leaf), Xylopia aethiopica (uda), and Ocimum gratissimum (scent leaf)), which they have acquired through Indigenous Knowledge Systems (IKS). Nevertheless, this ethno-biological knowledge is largely disconnected from formal educational settings. This study aimed to explore the degree to which the incorporation of Igbo ethno-biological knowledge into the teaching of challenging Biology topics enhances students' conceptual understanding, engagement, and long-term retention. A quasi-experimental pretest-posttest non-equivalent control group design was utilized. The participants consisted of 186 senior secondary school year two (SS2) students from four co-educational public schools located in Enugu and Anambra States (two experimental groups and two control groups). The experimental groups underwent a 6-week IKS-integrated Biology instruction, which included culturally contextualized lessons, indigenous classification tasks, ethno-medicinal plant analysis, and local ecological observations, while the control groups received traditional lecture-based instruction. The instruments used for assessment included the Biology Conceptual Understanding Test (BCUT, comprising 35 multiple-choice and 15 short-answer items, r=0.87), the Engagement Inventory (EI, a 5-point Likert scale, α=0.91), and the Delayed Retention Test (identical to the BCUT, administered 6 weeks after the intervention). Qualitative data were gathered from 12 focus group discussions to complement the quantitative findings. The results of the ANCOVA indicated that students in the IKS-integrated group significantly outperformed those in the control group in terms of conceptual understanding (mean experimental=72.4%, SD=9.6; control=48.3%, SD=11.2; F(1,183) =146.3, p<0.001, η²=0.44). Qualitative findings indicated that students perceived the integration of Indigenous Knowledge Systems (IKS) as